An evaluation of Quran memorization mobile app among middle-aged adults and early elderly / Siti Fatimah Abd Raof, Nor Azzyati Hashim, Noor Azura Zainuddin - Abd Raof, Siti Fatimah; Hashim, Nor Azzyati; Zainuddin, Noor Azura (UiTM Cawangan Perlis, 2019)
There are many mobile applications that help to boost Quran memorization, but the target users are normally for general people without specifically consider the design for ageing people. This becomes imperative since ageing people need to face with the cognitive and physical decline as they are getting older. Hence, to enhance Quran memorization, a mobile app known as E-Hafazan was developed. For the interface design, the researchers integrated the mobile design guidelines for ageing people that comprise of seven categories: cognitive, content, navigation, visual, audio, perception and dexterity. The aims of this paper are to investigate the usability of mobile interface design and user acceptance on E-Hafazan mobile app for Quran memorization. A total of 30 people around Arau, Perlis participated in the system evaluation. The participants were in the category of middle-aged adults and early elderly, between the ages of 40-74 years old. From the findings, most of the respondents are satisfied with the E-Hafazan app since it is effective, interactive and ubiquitous for memorizing Al-Quran although there is a slight lack in the result of the visual category for the mobile interface design.